Does the Canadian Economy suffer from Dutch Disease? - Michel Beine; Charles S. Bos; Serge Coulombe (Tinbergen Institute, 2009)
We argue that the failure to disentangle the evolution of the Canadian currency from the U.S. currency leads to potentially incorrect conclusions regarding the case of Dutch disease in Canada. We propose a new approach that is aimed at extracting both currency components and energy- and commodity-price components from observed exchange rates and prices. We first analyze the separate influence of commodity prices on the Canadian and the U.S. currency components. We then estimate the separate impact of the two currency components on the shares of manufacturing employment in Canada. We show that 42 per cent of the manufacturing employment loss that was due to exchange rate developments between 2002 and 2007 is related to the Dutch disease phenomenon. The remaining 58 per cent of the employment loss can be ascribed to the weakness of the U.S. currency.
Keywords: C11; F31; O13; O51; 330; Dutch disease; Natural resources; Exchange rates; Currency components; Bayesian econometrics; Rohstoffreichtum; Natürliche Ressourcen; Wechselkurs; Bayes-Statistik; Schätzung; Kanada